Hydrogen Production: Production of H2 by Ethanol Photoreforming on Au/TiO2 (Adv. Funct. Mater. 2/2014). (January 2014) - Puga, Alberto V.; Forneli, Amparo; García, Hermenegildo; Corma, Avelino
<x xml:space="preserve">Abstract</x> Materials based on gold nanoparticles supported on TiO2 are extremely efficient photocatalysts for the production of H2 from ethanol. On page 241, A. Corma and co‐workers achieve high production rates and selectivities (>99.3%) under simulated solar light. By using this technology, a photocatalytic process yielding a gaseous stream composed of almost pure H2 with the sun as the only energy source can be envisaged. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>